IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DI SEKOLAH DASAR ISLAM TERPADU (SDIT) MENARA FITRAH INDRALAYA KABUPATEN OGAN ILIR - Maghfir Maghfir (Conciencia, 2014)
AbstractThe research method used is the qualitative approach, which is based on the purpose to obtain a realistic picture-holistic concept of school-based management implementation in SDIT Tower Indralaya disposition. Source of data in the form of writing in this study is the source document in the form of books, scientific papers, as well as sheets of records pertaining to the research. Unwritten data source is the principal, teachers, and those who are considered related to the implementation of school-based management in SDIT Tower Indralaya disposition.Based on these results, several conclusions can be formulated, that implementsi School Based Management (SBM) in SDIT Tower Indralaya disposition includes several aspects. The first aspect of the curriculum with subjects and programs with a strong Islamic values. Both aspects of the interactive process, inspiring, fun, challenging, and motivations that conditioned their learning process students learn with berpartisifasi active and independent. These three aspects of the learners, which makes learners who Muttaqin intelligent, noble, and have the skills and interests for the benefit of mankind. The fourth aspect of educators to work in a professional manner and have the competence and positioning itself as a role model in school. These five aspects of infrastructure are complete enough to support the educational process. The sixth aspect of management through a clear plan, and executed with each other to form a single entity to coordinate between all components of the school. Ketuju aspects of financing, income funds of learners, BOS state budget, as well as community infaq managed with the standards set by JSIT. Eighth aspects of assessment through supervision and inspection conducted by the principal yng scheduled and evaluation of learning outcomes and programs undertaken by teachers. In general, the implementation of school-based management in SDIT Tower Indralaya disposition according to the author is good enough and able to balance the development of education today. Keywords: Curriculum, Process, Students, Educators and Educational Staff, Facilities and Infrastructure, Management, Financing, and Assessment.